Urbanization and Environmental Degradation in G7 Countries and Asean Countries - Leong, Su Ling (Universiti Malaysia Sarawak (UNIMAS), 2017)
The mam objective of this study is to identify the relationship of urbanization and environmental degradation in G7 countries (the United States of America, the United Kingdom, Gennany, Italy, France, Italy, Japan and Canada) and selected ASEAN countries (Malaysia, Indonesia, Thailand, Philippines, Vietnam and Cambodia) from year 1993 to 2014. STIRPAT model is employed to investigate the urbanization effect towards environmental degradation. The variables in STIRPAT model consist of total population, economic growth (GOP per capita) and energy intensity as the proxy of technology while urban population and trade openness are utilized as the proxy of urbanization. The --I methodology includes panel unit root test, panel cointegration tests and pooled mean group (PMG) estimator. The result suggests G7 countries is ahead of ASEAN countries in handling environmental issues. Hence, the policymakers in ASEAN countries should take the initiative to learn from developed countries such as G7 countries in implementing policies to reduce C02 emissions in the country.